Post-conflict recovery: Does the global economy work for peace? - Tony Addison (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Countries as diverse as Afghanistan, Angola, and Sierra Leone are now attempting to recover from major wars, often amidst continuing insecurity. The challenge is to achieve a broad-based recovery that benefits the majority of people. The economic and social recovery of conflict-affected countries cannot be separated from their interaction with the rest of the world through flows of finance, goods, and people. Unfortunately, the global economy is not working well for peace. Trade reform, in particular, must take account of the need to create better, and non-violent, livelihoods for the world's poor: rich-country protectionism in agriculture hinders broad-based recovery and thereby harms the new international security agenda. Post-conflict economies also need more external finance to support early institutional development and reform, thereby increasing the effectiveness of longer-term aid inflows.
Keywords: F02; F34; F35; 330; conflict; terrorism; international trade; global public goods; Politische Gewalt; Globalisierung; Politischer Konflikt